A history of economic thought in France
1 online resource.
Keywords: "Traditionally there has been a long and sustained interest in studying the history of economic ideas in France. Interest appeared to wane after World War II but in recent decades, there has been a marked renaissance of interest and research in the contributions of French-speaking authors. Drawing on the flow of recent research, this book presents a new assessment of the history of political economy in France incorporating both novel presentations of some traditional subjects and topics that are not usually studied. This second volume analyses the evolution of political economy during the long nineteenth century, combining an assessment of both liberals and their opponents. Its first part covers the most outstanding contributions to political economy in the age of industry, from the founding fathers (L.-C.-C. Destutt de Tracy and J. -B. Say) until the pre-World War I period, including that of A.-A. Cournot, J. Dupuit, the French liberal economists and L. Walras. The volume then outlines the critiques of liberal political economy, focusing on the analyses of J.-C.L.S. de Sismondi, C.-H. de Saint-Simon and his followers, and the successive generations of socialist and associationist authors, not forgetting the sociological critique. A substantial postlude concludes the volume with a survey of recent developments of French economic thought up to the present day. A History of Economic Thought in France will be invaluable reading for advanced students and researchers of the history of economic thought, political economy, intellectual history and French history"--